Reduced spread of influenza and other respiratory viral infections during the COVID-19 pandemic in southern Puerto Rico. - Talia M Quandelacy; Laura E Adams; Jorge Munoz; Gilberto A Santiago; Sarah Kada; Michael A Johansson; Luisa I Alvarado; Vanessa Rivera-Amill; Gabriela Paz-Bailey (PLoS ONE, 2022)
Introduction Impacts of COVID-19 mitigation measures on seasonal respiratory viruses is unknown in sub-tropical climates. Methods We compared weekly testing and test-positivity of respiratory infections in the 2019-2020 respiratory season to the 2012-2018 seasons in southern Puerto Rico using Wilcoxon signed rank tests. Results Compared to the average for the 2012-2018 seasons, test-positivity was significantly lower for Influenza A (p<0.001) & B (p<0.001), respiratory syncytial virus (RSV) (p<0.01), respiratory adenovirus (AdV) (p<0.05), and other respiratory viruses (p<0.001) following March 2020 COVID-19 stay at home orders. Conclusions Mitigation measures and behavioral social distancing choices may have reduced respiratory viral spread in southern Puerto Rico.